Направления мотивации и повышения производительности труда в условиях кризиса для обеспечения инвестиционной активности предприятий - Черная, А.А.; Брюховецкий, Я.С.; Лыгус, О.Е. (Стратегія і механізми регулювання промислового розвитку, 2017)
Представлены принципы отбора и оценки работников на уровне предприятия в условиях рынка и усиливающейся конкуренции за рабочие места в условиях кризиса. Обоснованы направления мотивации: уменьшение постоянной части оплаты труда, формирование благоприятного морально-психологического климата в коллективе, формирование у сотрудников чувства безопасности, уверенности в сохранении рабочих мест посредством проведения тренингов, обучающих семинаров, повышения квалификации сотрудников, что, в конечном итоге, содействует повышению производительности труда работников в кризисных условиях, сохранению персонала предприятия, формированию предпосылок для осуществления инвестиционной деятельности предприятий. Представлен опыт обучения кадров и повышения квалификации на крупных предприятиях (ДТЭК, Метинвест, ПАО «Запорожсталь», «Концерн Галнефтегаз»). Викладено принципи відбору й оцінки працівників на рівні підприємства в умовах ринку і конкуренції, що посилюється, за робочі місця в умовах кризи. Обґрунтовано напрями мотивації: зменшення постійної частки оплати праці, формування сприятливого морально-психологічного клімату в колективі, формування у співробітників відчуття безпеки, впевненості у збереженні робочих місць за допомогою проведення тренінгів, навчальних семінарів, підвищення кваліфікації співробітників, що, зрештою, сприяє підвищенню продуктивності праці працівників у кризових умовах, збереженню персоналу підприємства, формуванню передумов для здійснення інвестиційної діяльності підприємств. Наведено досвід навчання кадрів і підвищення кваліфікації на великих підприємствах (ДТЕК, Метінвест, ПАТ «Запоріжсталь», «Концерн Галнафтогаз»). The influence of the deterioration of the institutional environment under the conditions of cardinal changes on the investment activity of enterprises is shown.
The strengthening of competition in the conditions of the crisis and the reduction of the possibilities for investing in enterprises are substantiated.
Based on the analysis of the incomes of the population of Ukraine, a steady fall in real incomes, a further impoverishment of the population, a decrease in its purchasing power compared to 2013 are revealed. The increase in the minimum wage and pensions with the rapid growth of retail prices and utility tariffs doesn`t defray costs even for simple reproduction.
It was revealed that under conditions of narrowing of the internal market and production volumes, the system of motivation of labor of workers at industrial enterprises undergoes drastic changes. This applies to both material and moral motivational incentives and payments.
In times of crisis, approaches to personnel management and remuneration of labor are changing. The markets are narrowing, the rules of the game are changing. In these terms, it is very cautious to approach the issues of optimization (reduction) of the payroll to those enterprises whose personnel have been formed for more than one year. It is necessary to perfect the system of motivation in the direction of increasing labor productivity.
The principles of selection and estimation of employees at the enterprise level in the conditions of the market and increasing competition for jobs in crisis conditions are presented: objectivity; involvement; homogeneity; differentiation; confidentiality; independence of appraisers; regulation; accessibility of the database and assessment materials; awareness of workers on selection and evaluation criteria; feedback.
The directions of motivation and increase of labor productivity of employees in the conditions of the crisis are substantiated: reduction of the constant part of wages, formation of a favorable moral and psychological climate in the team, the formation of a sense of security among employees, confidence in preserving jobs through training, training seminars, advanced training, which ultimately contributes to raising the productivity of workers in crisis conditions, the preservation of the personnel of the enterprise, the formation of prerequisites for the implementation of investment activities of enterprises.
The experience of personnel training and advanced training is presented in such a major concerns as DTEK, Metinvest, Zaporizhstal, Concern Galneftegaz.
The realized measures on training, motivation and increase of labor productivity contribute to the expansion of investment activity of enterprises.